The family institution in the context of systemic risks: a Confucian alternative to postmodernism - Bachun, Alexei V. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article analyses the systemic risks threatening the family institution in the 21st century: demographic crisis, economic insecurity, cultural and moral shift, conflicting new gender expectations, ect. It is shown how the value and methodological resources of Confucianism can be used to mitigate them. It is noted that these risks mutually reinforce each other and form a system that undermines the stability of the family institution. A four-component strategy for preserving the institution of the family is proposed, based on the Confucian principles of true governance and personal example.
Keywords: family; marriage; family institution; demographic crisis; Confucianism; postmodernism; adverse childhood experiences; gender conflicts; social stability; traditional values